Pattern recognition and computer vision. first Chinese Conference, PRCV 2018, Guangzhou, China, November 23-26, 2018, Proceedings /: first Chinese Conference, PRCV 2018, Guangzhou, China, November 23-26, 2018, Proceedings. Part I : (2018) - Unknown
No abstract available